Substantive Majoritarian Consensual Democracy: A Critical Response to Matolino's Consensus as Democracy in Africa - Adeate, Tosin (Theoria (Pietermaritzburg), 2025)
Afro-communitarian thinkers have often pointed to consensual democracy as a valuable feature of traditional African societies. African philosophers, including Kwasi Wiredu and Bernard Matolino, have drawn attention to this pattern of political arrangement to consider what the political practice means for modern African politics. While Wiredu praissed consensual democracy and sought to explore how it could be relevant for contemporary African democratic development, Matolino finds it undesirable. In the book Consensus as Democracy in Africa, Matolino identifies several significant concerns with the theoretical and practical feasibility of consensual democracy, such as the concern with individual freedom. He rejects consensus as a viable democratic theory for modern African politics. In this article, I respond to Matolino's objection. My responses demonstrate a persuasion for a consensus-imbued majoritarian model of governance. While noting that consensus is conceptually reconcilable with party politics, I argue that a consensual orientation allows for expanded freedom of association that helps check abuse of party-political loyalty.